2019
DOI: 10.1136/archdischild-2019-317090
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric enteral feeding at home: an analysis of patient safety incidents

Abstract: AimsTo describe the nature and causes of patient safety incidents relating to care at home for children with enteral feeding devices.MethodsWe analysed incident data relating to paediatric nasogastric, gastrostomy or jejunostomy feeding at home from England and Wales’ National Reporting and Learning System between August 2012 and July 2017. Manual screening by two authors identified 274 incidents which met the inclusion criteria. Each report was descriptively analysed to identify the problems in the delivery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
0
18
0
4
Order By: Relevance
“…An adapted framework approach was used 15. An initial framework was created for problems in care, contributory factors and patient outcomes based on the framework used in a previous study by the same authors, which was developed by adapting existing frameworks for categorising problems in care, contributory factors and patient outcomes primarily in hospital settings 16. RFN and BP first independently coded 30 of the incidents identifying the problems in care, any stated contributory factors and any stated patient outcome.…”
Section: Methodsmentioning
confidence: 99%
“…An adapted framework approach was used 15. An initial framework was created for problems in care, contributory factors and patient outcomes based on the framework used in a previous study by the same authors, which was developed by adapting existing frameworks for categorising problems in care, contributory factors and patient outcomes primarily in hospital settings 16. RFN and BP first independently coded 30 of the incidents identifying the problems in care, any stated contributory factors and any stated patient outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Especially in complex care needs, such interventions proved to be helpful in reducing non-urgent or improper ED visits by helping PLOS ONE parents in treating the child condition at home [25,26]. Studies have further identified that priorities for safety practices at home, such as the training of family care givers, the provision and expertise of services in the community, and the availability and reliability of equipment are handovers between hospitals and community services [27][28][29]. During IPHC, the common procedures needed by patients often include blood sample collection, enteral feeding and intravenous medication administration, which have clear benefits when performed at home.…”
Section: Plos Onementioning
confidence: 99%
“…A key challenge is how to prepare and support parents to provide this specialist care. In an analysis of incident reports for children with feeding tubes, healthcare professionals identified inadequate training for family carers as a significant cause of concern, with some children coming to a harm as a result of inadequate training for families 7 . Our research on gastrostomy care has shown that many parents do not feel adequately prepared to provide the required care when they first go home after their child's surgery and many reported feeling very anxious.…”
Section: Introductionmentioning
confidence: 98%